Pengaruh Work Life Balance Pengembanga Karir dan Kepuasan Kerja Terhadap Loyalitas Karyawan Pada UD. Trinadi Garmen di Kabupaten Bangli - Darmayani, Ni Luh Ika; Sumartana, I Made; Herlambang, Putu Gede Denny (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
A company's success is directly tied to the dedication and effort of its personnel. The importance of cultivating employee loyalty and holding on to good employees is growing in today's competitive job market. One company or industry that relies on loyal employees is UD. Trinadi Garmen in Bangli Regency. Low levels of loyalty persist among UD. Trinadi Garmen employees. The goal of this study is to look at how UD. Trinadi Garmen in Bangli Regency deals with work-life balance, career growth, and job satisfaction in relation to employee loyalty. A total of 35 individuals from UD. Trinadi Garmen were included in the sample for this quantitative investigation, which utilised saturated samples as its sampling method. For this investigation, SPSS version 25 for Windows was used for data processing. Multiple linear regression analysis, the coefficient of determination test, the F-test, the t-test, the research instrument validity and reliability test, and the classical assumption test are all used in the data analysis process. Employee loyalty is positively and significantly impacted, in part, and simultaneously, by work-life balance, career advancement, and job satisfaction.